SKIN INJURY SURFACE CYTOLOGY DYNAMICS CHANGES IN EXPERIMENTAL WOUND PROCESS - Muraviov, P.Т.; Bespalko, М.H.; Zaporozhchenko, B.S. (World of Medicine and Biology, 2025)
Long-persisting chronic wounds represent a significant challenge for general surgery specialists. The purpose of the study was to determine the characteristics of cellular composition changes along the wound surface during post-traumatic regeneration under the conditions of combined application of collagen hydrolysate in an experimental setting. Experimental studies were performed on the model of Voltran Ekol ES55 pneumatic weapon induced gunshot wound. Collagen hydrolysate was additionally included to complex wounds’ therapy. The efficacy of wounds’ healing was estimated morphologically and immunohistochemically. The main group rats (13 (43.3 %)) were treated with a collagen hydrolysate, meanwhile the comparison group rats (17 (56.7 %)) – without. On the 7th day, CD45+ infiltrate was expressed in both groups, while CD68+ cells were found in greater amount in the main group. On the 14th day, CD68+ cells were detected in the inlet zone in both groups, but in the main group their amount was lesser. CD163+ cells were verified in both groups as scattered single cells. Verification of CD45+ cells on the 14th day revealed isolated positive cells scattered among fibrous tissue in both experimental groups. On the 28th day quite a few CD68+ cells were detected in the superficial layers of the scar in the main group, that was unsimilar to the comparison one. The authors supposed the data obtained are the experimental evidence of collagen hydrolysate clinical efficacy testing reasonability for wound healing outcomes improving.
Keywords: rat; wound; cytology; regeneration; wound process; collagen hydrolysate; wound treatment